Planejamento educacional individualizado na educação especial: propostas oficiais da Itália, França, Estados Unidos e Espanha - Valadão, Gabriela Tannús (2010)
The Salamanca Statement (1994) advocated the practice of schooling for people with disabilities in the regular classroom and into mainstream schools, stressing the need to optimize the planning tool into pedagogic practices in order to meet the special educational needs of some students within heterogeneous classrooms. In several European and North American countries, the oficialization of the individual education practice plan is one of the intervention tools used to improve the students with disabilities education. Although the names used for this practice vary between countries and terms such as plan/planning/project, educational/scholastic/ enrollment, and personalized/individual are largely employed, these proposals focus on the existence of legal provisions to ensure to all students in situation of disability the right to an individual educational plan (IEP) tailored to meet their individual needs. There is no legal requirement for this issue in Brazil. This lack explains some of the current problems outlined by the inclusive policy and practice in our education system. This paper aimed to describe, analyze and compare the IEP proposals adopted by Italy, France, U.S., and Spain, seeking to comprehend the IEP regulation in these countries and to identify parameters to elaborate proposals enlightening the paths to follow to implement this practice in Brazil. It was a documentary study based on available data from the official websites of the Ministry of Education in those countries between 1994 and 2008. The applied methodology envolved the following stages: 1) preliminary feasibility study for a research proposal; 2) search, identification, and selection of official documents; 3) content analysis of documents related to the practice of IEP; 4) data organization; and, 5) data description and analysis. The results showed diversity between countries including the concept of school inclusion, the radical and/or total inclusion and the inclusion that presumes the existence of the continuum of support services. They also presented the variety in models of IEP from those who relate solely to the schooling to those who contemplate a more widespread attention beyond the realm of school life. The conclusions highlight the importance of legal provisions on the implementation of the IEP for students with disabilities to ensure the right of school education.